In vitro comparison of conventional surgical and rotary ultrasonic bone drilling techniques. (April 2020) - Gupta, Vishal; Singh, Ravinder Pal; Pandey, Pulak M; Gupta, Ravi
In orthopedic and trauma surgical operations, drilling of bone is one of the commonly used procedures performed in hospitals and is a clinical practice for fixing the fractured parts of human bones. Force, torque and temperature play a significant role during the bone drilling and decide the stability of the medical implants. Therefore, it is necessary to minimize force, torque and temperature while drilling to avoid the thermal necrosis and osteosynthesis. This study focused on studying the influence of various types of bone drilling parameters (rotational speed, feed rate, drill diameter and ultrasonic amplitude), tools (solid tool, hollow tool and conventional twist drill bit) and techniques (conventional surgical drilling, rotary ultrasonic bone drilling and rotary bone drilling) on force, torque, temperature and microcracks produced in the drilled surface of the bone. The experimental investigations were conducted on porcine bone samples to perform the comparative study. Results revealed that increasing the diameter of drill tool and feed rate results in the increase in force, torque and temperature, while low rotational speed (500 r/min) generated a low temperature, high cutting force and torque for all types of drilling processes and tools evaluated in this study. Experimental results also revealed that rotary ultrasonic bone drilling with hollow tool generated the lowest cutting force, torque, temperature (<47 °C) and microcracks in the drilled surface of the bone as compared to the other four types of drilling techniques evaluated in this study. Influence of external irrigation technique on temperature was also studied with respect to the rotary ultrasonic bone drilling with a hollow tool, which could eliminate the problem of thermal necrosis. In conclusion, this study revealed that the rotary ultrasonic bone drilling process with hollow tool produced lesser cutting force as compared to rotary bone drilling and conventional surgical drilling for hollow and solid tools. The study also revealed that rotary ultrasonic bone drilling process has the potential to minimize the cutting force, torque and temperature as compared to the conventional surgical drilling for orthopedic surgery.